2010
DOI: 10.1186/1757-1146-3-12
|View full text |Cite
|
Sign up to set email alerts
|

The rheumatoid foot: a systematic literature review of patient‐reported outcome measures

Abstract: BackgroundThe foot is often the first area of the body to be systematically affected by rheumatoid arthritis. The multidimensional consequences of foot problems for patients can be subjectively evaluated using patient-reported outcome measures (PROMs). However, there is currently no systematic review which has focused specifically upon the PROMs available for the foot with rheumatoid arthritis. The aim of this systematic review was to appraise the foot-specific PROMs available for the assessment and/or evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 75 publications
0
39
0
7
Order By: Relevance
“…As Guyatt and Deyo remarked, the answer on the anchor question will never solitarily rely on operative outcome, but subsequently measures satisfaction with the program, rehabilitation process, or desire to show gratitude to those who have spent time and effort trying to help the patient [7]. The FFI questionnaire is an attractive measurement for physicians who wish to have a sensitive, reliable and responsive questionnaire for routine clinical practice [26].…”
Section: Discussionmentioning
confidence: 99%
“…As Guyatt and Deyo remarked, the answer on the anchor question will never solitarily rely on operative outcome, but subsequently measures satisfaction with the program, rehabilitation process, or desire to show gratitude to those who have spent time and effort trying to help the patient [7]. The FFI questionnaire is an attractive measurement for physicians who wish to have a sensitive, reliable and responsive questionnaire for routine clinical practice [26].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the responsiveness of the MFPDQ has yet to be clearly demonstrated and provision for clinical interpretability is similarly lacking. Walmsley et al (2010) suggested that this tool might be more useful in non-RA populations.…”
Section: The Manchester Foot Pain and Disability Questionnairementioning
confidence: 99%
“…In their review of patient-reported measures, Walmsley et al (2010) identified a need to develop an RA-disease and foot-specific tool with a greater emphasis on a bio-psychosocial conceptual basis. The Salford Arthritis Foot Evaluation (SAFE) (Walmsley et al 2012) tool incorporates the development of items that have meaning to both the patient and clinician.…”
Section: The Salford Arthritis Foot Evaluation Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerous consequences of living with feet affected by RA can be assessed and evaluated using a class of subjective outcome measures known as patient-reported outcome measures (PROMs) [7]. The Darzi report [8] has recommended the use of PROMs to provide a greater focus on the patient-centered perspective.…”
Section: Introductionmentioning
confidence: 99%